Pelatihan Manajemen Bencana Bagi Anggota Padjadjaran Nursing Corps (PNC) - Anna, Anastasia; Prawesti, Ayu; Emaliyawati, Etika; Mirwanti, Ristina (BAGIMU NEGERI : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
The high and varied disasters occur in Indonesia, requiring the government and the whole community to be ready for disaster. In the Faculty of Nursing Universitas Padjadjaran (Unpad), there is a group of students who do extracurricular activities to provide health aid called PNC. Training needs to be done to enhance the role of PNC as well as increasing the participation of students in the disaster relief program. This training resulted in increased knowledge and attitudes of PNC members on disaster management, and also increased the knowledge and attitude related to the role and function of students in disaster management effort. In addition, other additional results related to the effectiveness of training methods for PNC members successfully obtained. The methods compared were lecture and discussion (LD) compared with LD plus simulation and FGD methods. It is measured by using the quasi experimental method with pretest-posttest control group design. Data analysis used Mann Whitney test. The result showed that there was no difference in knowledge and attitude (p = 1,000) in both treatment groups (p = 0,424). Which means that there was no difference between LD method and LD plus simulation and FGD method.Keywords: Training, Disaster Management, Padjadjaran Nursing Corps (PNC)